PERANAN WARGA STANPLAT GIRANG DALAM MENYAMBUT WISATAWAN DI DESA INDRAGIRI KABUPATEN BANDUNG - Syahlevie, Nor; Pringgabayu, Dematria; Bambang Nurcahya, Said (LPPM Politeknik Pajajaran ICB Bandung, 2022)
The people of dusun Stanpat Girang Indragiri Village, Rancabali District, Bandung Regency are a community of tea plantation workers under PTPN VIII with the main activity of cultivating tea plants in the Rancabali sub-district. The development of immigrant communities with natives from around southern Bandung creates cultural diversity that affects the art of building and architectural styles of buildings. The beautiful nature in this plantation area is very attractive for immigrants to enjoy nature, and stop for a while to enjoy a meal in the cool air. This interaction and integration has led to a change in service according to the demands of migrants to become a warung that provides food with vegetables and traditional side dishes such as fish, chicken, birds and transforms into providing shelter, lodging and hotels. The potential natural tourist attraction of the Ciwidey and Rancabali areas is attractive because it is supported by supporting infrastructure and facilities such as gas stations, hotels, restaurants, and places of worship and the construction of the Seroja toll road that connects Soreang to the city of Bandung makes tourists come faster. Cultural attractions are also often held in tourism areas such as there Pateggan, Kawah Putih, Ciwalini Hot Springs, Rancaupas, and other new tours. Dusun Stanplat takes a market approach by presenting traditional concepts of cultural attractions and natural landscapes that are beautified by natural ornament buildings so that they are liked by the motorcycle community, car community and other communities to live and enjoy the beauty and cultural friendliness and make interactions between tourists and residents more fluid, cooking programs and stay in a traditional house with the locals and away from the hustle and bustle of the big city.